Complete mitochondrial genome of Cotton Leaf Roller Haritalodes derogata (Lepidoptera: Crambidae). (3rd July 2016) - Zhao, Jing; Sun, Yang; Xiao, Liubin; Tan, Yongan; Bai, Lixin
Abstract: Haritalodes derogata (Lepidoptera: Crambidae) has been recorded as an important pest of cotton in many countries of the world. In this study, the complete mitochondrial (mt) genome of Cotton Leaf Roller Haritalodes derogata is determined, which is 15, 253 bp in length (GenBank accession number: KC515397) containing 37 typical animal mitochondrial gene and an A + T-rich region. The gene order of H. derogata mtDNA was different from the insect ancestral gene order in the translocation of trnM, as shared by previously sequenced lepidopteran mtDNAs. The protein-coding genes (PCGs) have typical mitochondrial start codons ATN, with the exception of COI, Nad5, which uses the start codons CGA, GTT. In addition, five of 13 PCGs harbor the incomplete termination codons, a single T. All of the tRNA genes had typical cloverleaf secondary structures except for trnS1(AGN) . Like other lepidopteran mtgenomes, the control region is located between rrnS and trnM with a length of 329 bp and an A + T content of 96%, which is the most AT-rich region and habors a conserved structure combining the motif ATAGA and a 14-bp poly-T stretch. Both maximum likelihood and Bayesian inference analyses highly support a sister-group relationship: Pyraustinae + (Spilomelinae + (Acentropina (Crambine + Schoenobiine))).